2017
DOI: 10.3329/sja.v14i2.31244
|View full text |Cite
|
Sign up to set email alerts
|

Water use efficiency and yield of cowpea and nutrient loss in lysimeter experiment under varying water table depth, irrigation schedules and irrigation method

Abstract: ABSTRACT. Significant nutrients uptake response was observed owing to variation in water table depth, irrigation schedules and methods. Analysis of lysimeter leached water showed that with deep drainage and more IW:CPE, leaching losses of N,P and K were more however water applied through sprinkler saved 20.1, 53.7 and 24.4% N, P and K, respectively, over flooded method. Irrigation given at IW: CPE 0.3 through sprinkler form at 60±1.5 cm water table depth favours the higher grain yield and nutrient uptake by cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Dasila et al . 11 showed that WUE in flooded irrigation conditions is very low, due to serious water and nutrient losses. A further complication is that an excess of soil water may not immediately exit the system, but may remain in the B horizon of texture-contrast soils as a perched water table 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Dasila et al . 11 showed that WUE in flooded irrigation conditions is very low, due to serious water and nutrient losses. A further complication is that an excess of soil water may not immediately exit the system, but may remain in the B horizon of texture-contrast soils as a perched water table 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Nodulation parameters responded significantly only to main effect of irrigation frequency but not to main effect of intra row spacing and its interaction with irrigation frequency. All nodulation parameters were significantly increased with increase in irrigation frequency [ 3] which might be related to better availability of soil moisture with frequent irrigation [14].…”
Section: Nodulationmentioning
confidence: 99%
“…The ensuing rise in soil moisture during the haricot bean growth stages improved plant growth, which led to the subsequent increase in PH. Dasila et al (2017) also reported that increasing irrigation frequency maintains soil moisture availability and increases PH. Wube et al (2020) found that the treatment with no SI resulted in the minimum PH, while applying SI only at the emergence, pod formation and grain filling stages also resulted in low PH.…”
Section: Resultsmentioning
confidence: 94%